English Language Borrowing in Sasak Language Performed by Teachers on What’s App Group - Satria, Ozi (MASALIQ, 2021)
This research purposed to identify English words borrowing in Sasak language and classified their phonological processes. This research implied documentary research method. In which, the researcher only captured, observed, collected, copied, and gave codes to the gained data thence analyzed them using descriptive qualitative research method, the technique used was in accordance to Fasold, Hoffer, and Katamba theories in keeping with the four categories of words borrowing such as loanword, loanshift, calque, and loanblend. He further adopted the claimed concepts by Fromkin, Crystal, Aor in relation with the phonological processes particularly in terms of supra-segmental phonology. They classified the processes of supra-segmental phonology into assimilation, dissimilation, elision, epenthesis, metathesis, spoonerism, nasalization, palatilisation. To respond the first focus of this research, the researcher found that thirty words belonged to loanwords, only one judged as loanshift, three words claimed as calque, and the rest one of the whole found words was distinguished as loanblend. The further analysis result was responding the second focus of this research. In which, the researcher classified the phonological processes of English words borrowing in Sasak language. He gained seven borrowed words which distinguished by way of assimilation process, four borrowed words were included to dissimilation, six were implied to elision, eleven of them grouped to epenthesis, he further found only one belonged to metathesis, and he greatly obtained updated process of supra-segmental phonology due to the rest quantity of the borrowed words were not included to any processes of supra-segmental phonology. Those findings were significantly clarified valuable contribution in relation to provide updated knowledge of borrowing linguistic items from one language into another language particularly, English words in Sasak language performed by teachers on what’s app group namely, YPP. NURUL ISLAH BELEKA.